Exploring the effects of ursodeoxycholic acid-probiotic combination on Lactobacillus and liver enzyme levels for cholestasis management: An experimental study - Nur, Muhammad Hasbi; Lestari, Endang Sri; Budiono, Bernadus Parish; Prasetyo, Sigit Adi; Muniroh, Muflihatul (Faculty of Medicine, Universitas Islam Indonesia, 2024)
Background: Cholestasis arises from compromised bile secretion due to hepatocyte dysfunction, leading to liver impairment. Available treatments show limited efficacy, with ursodeoxycholic acid (UDCA) being a primary option. Cholestatic conditions influence gut microbiota; therefore, probiotic therapy emerges as a potential approach. Objective: This investigation aimed to evaluate the impact of combined administration of probiotics and UDCA on Lactobacillus levels, as well as the levels of the enzymes aspartate aminotransferase (AST) and alanine aminotransferase (ALT) in rats with restricted common bile ducts .Methods: A total of 35 male Sprague Dawley rats were randomly assigned to 7 groups, each comprising 5 members: K1 (healthy control), K2 (negative control with cholestasis), K3 (positive control with cholestasis given UDCA), K4 (cholestasis given 36 mg probiotics), K5 (cholestasis given 18 mg probiotics and UDCA), K6 (cholestasis given 36 mg probiotics and UDCA), and K7 (cholestasis given 54 mg probiotics and UDCA). The treatment duration was 21 days, during which blood samples were collected for AST and ALT analysis. Lactobacillus count was determined by quantitative polymerase chain reaction (PCR) analysis of fecal samples.Results: When UDCA and probiotics were given together in three different dosages, the Lactobacillus count significantly increased (p<0.05) compared to the other groups. Furthermore, compared to the other treatment groups, the UDCA-probiotic combination group exhibited noticeably lower AST and ALT values.Conclusion: Combining UDCA and probiotics elevated Lactobacillus count and decreased AST and ALT levels in cases of cholestasis more effectively than single therapy.